2022
DOI: 10.1039/d2cc04013a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-mediated three-component bioconjugation of amino- and azidosaccharides in ionic liquids

Abstract: Bioconjugation of carbohydrates have been a challenging task because of their chemical, functional, and structural diversities, and no single chemical modification tool can be universally applicable to all the target...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Reactions conducted under an atmosphere of 13 CO 2 , in which no 13 C incorporation was observed (Figure S65-S66), ruled out atmospheric CO 2 as the source of the linchpin carbon in the product. [47][48][49][50][51] Regarding the reaction mechanism (Figure 8a), there is scattered precedent for related transformations with mesyl chloride and its derivatives (e.g. 52').…”
Section: Methodsmentioning
confidence: 99%
“…Reactions conducted under an atmosphere of 13 CO 2 , in which no 13 C incorporation was observed (Figure S65-S66), ruled out atmospheric CO 2 as the source of the linchpin carbon in the product. [47][48][49][50][51] Regarding the reaction mechanism (Figure 8a), there is scattered precedent for related transformations with mesyl chloride and its derivatives (e.g. 52').…”
Section: Methodsmentioning
confidence: 99%
“…Despite the undeniable challenges of bioconjugation processes in aqueous media, efforts to discover alternative reaction media that are conducive to both bioconjugation reactions and stabilization of proteins have delivered little. Our research program, termed as Bioconjugation In Nonaqueous-Driven Reaction Solvent (BINDRS), has been pursuing novel bioconjugation technologies in nonaqueous media such as ionic liquids, and we hypothesized that HFIP would be a suitable candidate as a biomolecule- and organic chemistry reaction-compatible solvent for nonaqueous bioconjugation strategies (Figure A). HFIP and other fluorinated alcohols such as trifluoroethanol have been known to induce a certain secondary structure in peptide (formation of a helicoidal structure) due to their hydrogen-bonding capability, increased acidity of their hydroxyl group, and a high dielectric constant .…”
Section: Introductionmentioning
confidence: 99%
“…14 Previously, we reported that an aza-Wittig intermediate (iminophosphorane) can induce amine-azide-CO 2 three-component coupling in ionic liquids to form a stable urea linkage on biomolecules such as peptides/proteins, 15,16 DNAs, 17,18 and saccharides. 19 While other aza-Wittig and Wittig reagents were examined for ionic liquid-based bioconjugation, a Wittig reagent precursor with an aldehyde functional group turned out to be active for condensation reactions with amine groups forming an enamine linkage (Fig. 1A and C).…”
mentioning
confidence: 99%